2017
DOI: 10.1051/0004-6361/201629099
|View full text |Cite
|
Sign up to set email alerts
|

Millimeter radiation from a 3D model of the solar atmosphere

Abstract: Aims. We use state-of-the-art, three-dimensional non-local thermodynamic equilibrium (non-LTE) radiative magnetohydrodynamic simulations of the quiet solar atmosphere to carry out detailed tests of chromospheric magnetic field diagnostics from free-free radiation at millimeter and submillimeter wavelengths (mm/submm). Methods. The vertical component of the magnetic field was deduced from the mm/submm brightness spectra and the degree of circular polarization synthesized at millimeter frequencies. We used the f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 49 publications
3
40
0
2
Order By: Relevance
“…Preliminary results from advanced numerical models (e.g., those computed with the Bifrost model; Gudiksen et al 2011see also Carlsson et al 2016 and references therein) of quiet-Sun conditions indicate that the Mg II h2v feature forms in the middle chromosphere over a range of heights from 600 to 2000 km with a peak around 1400 km (Leenaarts et al 2013b). Synthetic observables calculated from the Bifrost at a wavelength of 1.3 mm, near that reported here, suggest that the radiation mostly originates at similar heights, with a peak at 1150 km (Loukitcheva et al 2017). While the diagnostics are formed in roughly the same region of the atmosphere, it is unclear whether there are systematic differences in formation height along individual lines of sight.…”
Section: Resultssupporting
confidence: 78%
“…Preliminary results from advanced numerical models (e.g., those computed with the Bifrost model; Gudiksen et al 2011see also Carlsson et al 2016 and references therein) of quiet-Sun conditions indicate that the Mg II h2v feature forms in the middle chromosphere over a range of heights from 600 to 2000 km with a peak around 1400 km (Leenaarts et al 2013b). Synthetic observables calculated from the Bifrost at a wavelength of 1.3 mm, near that reported here, suggest that the radiation mostly originates at similar heights, with a peak at 1150 km (Loukitcheva et al 2017). While the diagnostics are formed in roughly the same region of the atmosphere, it is unclear whether there are systematic differences in formation height along individual lines of sight.…”
Section: Resultssupporting
confidence: 78%
“…The spatial resolution of the simulations is subarcsecond, and so it is not straightforward to compare their results with the much poorer spatial resolution of the single-dish data. They find average brightness temperatures of 5000 K at 230 GHz and 6200 K at 94 GHz, corresponding to effective heights above the photosphere of about 1150 km at 230 GHz and 1600 km at 94 GHz (Loukitcheva et al, 2017). Earlier simulations of inter-network quiet-Sun regions by Wedemeyer-Böhm et al (2007) found even lower average brightness temperatures.…”
Section: Solar Brightness Temperaturesmentioning
confidence: 92%
“…The ALMA values are consistent with previous data, but with much smaller uncertainty due to the large number of values involved in our assessment. Loukitcheva et al (2015Loukitcheva et al ( , 2017 use state-of-the-art radiative hydrodynamic simulations of the solar chromosphere (from the Bifrost code; Carlsson et al, 2016) to predict brightness temperatures at millimeter wavelengths. The spatial resolution of the simulations is subarcsecond, and so it is not straightforward to compare their results with the much poorer spatial resolution of the single-dish data.…”
Section: Solar Brightness Temperaturesmentioning
confidence: 99%
“…Поскольку масштаб мелкомасштабной структуры внутри заданного куба много меньше размеров куба, то получаемое при таком построении распределение параметров атмосферы спокойного Солнца, практически, не нарушает общности расчетов. При расчете теплового тормозного миллиметрового излучения применялся алгоритм, использованный в [16].…”
Section: Doi: 1031725/0552-5829-2019-403-406unclassified